Teaching About Evolution and the Nature of Science.
Presents "Teaching About Evolution and the Nature of Science," published by the National Academy Press for the National Academy of Sciences Working Group on Teaching Evolution. Details major themes in evolution and selecting instructional materials. Includes appendices, a FAQ section, and a list of recommended reading materials.